2000
DOI: 10.1164/ajrccm.162.6.2004022
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Contact Investigations of Infectious Tuberculosis Patients

Abstract: The objective of this study was to describe outcomes of tuberculosis (TB) contact investigations, factors correlated with those outcomes, and current successes and ways to improve TB contact investigations. We abstracted clinic records of a representative U.S. urban sample of 1,080 pulmonary, sputum-smear(+) TB patients reported to CDC July 1996 through June 1997 and the cohort of their 6,225 close contacts. We found a median of four close contacts per patient. Fewer contacts were identified for homeless patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
135
4
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(154 citation statements)
references
References 7 publications
10
135
4
5
Order By: Relevance
“…(10) The result of an investigation of contacts of patients with tuberculosis in public health clinics in the USA demonstrated, on average, four close contacts per patient, of whom 2% had active tuberculosis, and the contact was more frequent among individuals in the same household and children under six years of age. (11) In the present study, we found that the contacts were predominantly adults, which agrees with the literature showing that tuberculosis principally affects people between 15 and 59 years of age. (1) The combination of the age of the cases with the production of infection in the group is due both to the greater number of contacts and to the greater risk of infection of the latter, together with the age of the source.…”
Section: Discussionsupporting
confidence: 93%
“…(10) The result of an investigation of contacts of patients with tuberculosis in public health clinics in the USA demonstrated, on average, four close contacts per patient, of whom 2% had active tuberculosis, and the contact was more frequent among individuals in the same household and children under six years of age. (11) In the present study, we found that the contacts were predominantly adults, which agrees with the literature showing that tuberculosis principally affects people between 15 and 59 years of age. (1) The combination of the age of the cases with the production of infection in the group is due both to the greater number of contacts and to the greater risk of infection of the latter, together with the age of the source.…”
Section: Discussionsupporting
confidence: 93%
“…4,5 However, contacts identified during a contact investigation may also have a history of a prior positive tuberculin skin test (TST) result; one study found that 10 % of contacts had a prior positive TST. 6 Until recently, the risk for such individuals to develop active TB disease was unknown, 7 and guidelines do not make specific treatment recommendations for contacts with a prior positive TST, except to state that decisions to treat must be individualized. 1 The challenge of evaluating contacts with a prior positive TST result is of particular concern to health departments that serve communities with substantial foreign-born populations, such New York City (NYC).…”
Section: Introductionmentioning
confidence: 99%
“…This low proportion (9.5%) is in stark contrast to the USA where, mainly as a result of policy directives in line with the goal of TB elimination in the USA [6], 74-79% of patients diagnosed with LTBI commence treatment [7,8]. In our cohort of contacts, low treatment rates for LTBI appeared to be mainly a consequence of physicians' reluctance to offer LTBI treatment rather than low patient uptake of treatment.…”
Section: To the Editormentioning
confidence: 62%
“…Diverse chemical and biological substances, including autologous blood [2], talc [3,4], fibrin [5] and antibiotics [6], have demonstrated various efficiencies to treat PAL. Recently, an endobronchial valve (EBV) was successfully utilised to treat PAL [7][8][9]. Targeting the lung lobe or segment with an air leak is a prerequisite for stopping PAL using EBV.…”
Section: To the Editormentioning
confidence: 99%